2020
DOI: 10.1093/mnras/staa3680
|View full text |Cite
|
Sign up to set email alerts
|

Is diffuse intracluster light a good tracer of the galaxy cluster matter distribution?

Abstract: We explore the relation between diffuse intracluster light (central galaxy included) and the galaxy cluster (baryonic and dark) matter distribution using a sample of 528 clusters at 0.2 ≤ z ≤ 0.35 found in the Dark Energy Survey (DES) Year 1 data. The surface brightness of the diffuse light shows an increasing dependence on cluster total mass at larger radius, and appears to be self-similar with a universal radial dependence after scaling by cluster radius. We also compare the diffuse light radial profiles to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 59 publications
2
46
0
Order By: Relevance
“…They also found the similarity of these distributions. The results of Montes & Trujillo (2019) and Sampaio-Santos et al (2020) are confirmed by recent N-body simulations (Alonso Asensio et al 2020).…”
Section: Introductionsupporting
confidence: 77%
“…They also found the similarity of these distributions. The results of Montes & Trujillo (2019) and Sampaio-Santos et al (2020) are confirmed by recent N-body simulations (Alonso Asensio et al 2020).…”
Section: Introductionsupporting
confidence: 77%
“…We have seen above that the ICL is dynamically bound to the host cluster, and we know from several studies that more massive haloes host the most massive BCGs ( [4,89,121,132,133] and others), which means that both growths of ICL and BCG are linked to the host cluster. It is, then, reasonable to expect BCG and ICL to co-evolve at some time during their assembly.…”
Section: Bcg-icl Evolutionmentioning
confidence: 96%
“…This year (2021) has been, so far, very fruitful on this topic. Sampaio-Santos et al [89] explored the connection between BCG + ICL and the total cluster mass distributions by using a sample of more than 500 clusters between redshift 0.2 < z < 0.35 from the Dark Energy Survey. Similarly to Zhang et al [10], who also used a sample (but smaller) from the same survey, found that the surface brightness of the BCG + ICL has a universal radial dependence after scaling it by cluster radius.…”
Section: Icl: An Observable Tracer Of the Dark Matter Distributionmentioning
confidence: 99%
See 2 more Smart Citations